Individual and corporate social responsibility: redemption from excessive executive pay? - Chen, Qiu (Journal of business ethics, 2025)
In this study, we examine the individual social responsibility of corporate executives in the context of excessive executive pay and further explore whether executives’ individual social responsibility can translate into their firms' corporate social responsibility (CSR). Given the morally charged discussion surrounding excessive executive pay, we analyze the research questions through the lens of social-psychological theories of morality. We find that executives' individual social responsibility in the form of personal donations is a responsive moral cleansing action that executives take to restore their threatened moral self-image due to the public disclosure of their excessive pay. However, executives who make personal donations to charities do not engage their corporations in more CSR activities. The findings demonstrate that corporate executives' individual social responsibility does not necessarily translate into corporate social responsibility. We attribute the lack of transferability from individual to corporate social responsibility to the compensatory nature of morality.